2006
DOI: 10.1083/jcb.200604011
|View full text |Cite
|
Sign up to set email alerts
|

Actin depolymerization is sufficient to induce programmed cell death in self-incompatible pollen

Abstract: Self-incompatibility (SI) prevents inbreeding through specific recognition and rejection of incompatible pollen. In incompatible Papaver rhoeas pollen, SI triggers a Ca2+ signaling cascade, resulting in the inhibition of tip growth, actin depolymerization, and programmed cell death (PCD). We investigated whether actin dynamics were implicated in regulating PCD. Using the actin-stabilizing and depolymerizing drugs jasplakinolide (Jasp) and latrunculin B, we demonstrate that changes in actin filament levels or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
142
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 50 publications
7
142
0
Order By: Relevance
“…If ataxin-2 is overexpressed in yeast it causes premature cell death due to defects in actin filament formation (Satterfield et al 2002). Actin depolymerisation has been shown to be an adequate cause of cell death in pollen tubes (Thomas et al 2006), suggesting that the relation between cell death and lack of actin structure is also present in angiosperms. It is not clear if the presently observed induction of ataxin-2 in Ipomoea petals is also an essential part of the process leading to cell death.…”
Section: Appearance Of Senescence Parameters Compared With Gene Exprementioning
confidence: 99%
“…If ataxin-2 is overexpressed in yeast it causes premature cell death due to defects in actin filament formation (Satterfield et al 2002). Actin depolymerisation has been shown to be an adequate cause of cell death in pollen tubes (Thomas et al 2006), suggesting that the relation between cell death and lack of actin structure is also present in angiosperms. It is not clear if the presently observed induction of ataxin-2 in Ipomoea petals is also an essential part of the process leading to cell death.…”
Section: Appearance Of Senescence Parameters Compared With Gene Exprementioning
confidence: 99%
“…SI activates PCD specifically in incompatible pollen, thereby preventing self-fertilization. Recent investigations revealed that alterations in actin dynamics can push pollen tubes into PCD (Thomas et al, 2006), and an SI-activated mitogen-activated protein kinase (Rudd et al, 1996) is implicated in signaling to PCD . These data suggest that in Papaver, these components contribute to an integrated SI signaling network to achieve inhibition and death of incompatible pollen.…”
mentioning
confidence: 99%
“…This fi nding suggested that disturbance of actin polymer dynamics could trigger PCD in pollen. Data implicated actin depolymerization being functionally involved in the initiation of SI-induced PCD and established a causal link between actin polymerization status and initiation of PCD in plant cells (Thomas et al 2006 ). Thus, the rapid and substantial actin depolymerization triggered by SI signaling not only results in the rapid inhibition of incompatible pollen tip growth, but it also activates a caspase-3-like/ DEVDase activity, triggering PCD (see Fig.…”
Section: Involvement Of Actin Signaling In Si-mediated Pcdmentioning
confidence: 99%
“…Both actin and microtubule alterations are implicated in mediating PCD (Thomas et al 2006 ;Poulter et al 2008 ). A number of studies have shown that either actin depolymerization or stabilization can infl uence whether a eukaryotic cell enters into an apoptotic pathway; see (Franklin-Tong and Gourlay 2008 ;Smertenko and Franklin-Tong 2011 ).…”
Section: Involvement Of Actin Signaling In Si-mediated Pcdmentioning
confidence: 99%
See 1 more Smart Citation